Honey bee as a model organism to study gut microbiota and diseases - Wang, Xiaofei; Zhang, Xue; Zhang, Zijing; Lang, Haoyu; Zheng, Hao (Drug discovery today. Disease models, 2018)
Honey bee is used to model behavior, brain function, and life history transitions, and the physiology, genetics evolution, social behaviors have been intensively studied in this model organism. Recently, it shows that honeybees offer a particularly good opportunity to study the interactions between host biology and gut microbiota that are limited in complexity. All core members of the community are exclusive to this gut system, which are important to the host metabolism, endocrine signaling, and immune system as known in other animal-microbe symbioses. Like other comparatively simple insect model organisms that have been widely used for human disease, honey bees have the homologous or analogous organs, such as brain, fat body, oenocytes, gastrointestinal tract, and circulatory system, thus highlighting the bee a promising subject to model human diseases, in particular for understanding the role of microbiome in health and disease.